Biocrust belt below the edge of a dying glacier in the Tropical Andes - Alejandro Salazar; Maria E. Gutiérrez-Lagoueyte; Ingibjörg S. Jónsdóttir; Isabel C. Barrio; Heiðrún I. Guðmundsdóttir; Emilio Rodriguez-Caballero; Adriana Sanchez (Alpine Botany, 2026)
On recently deglaciated terrain, soil instability can be a physical barrier limiting seedling establishment. Here we used a space-for-time approach to study the role of biological soil crust (biocrust) as soil surface stabilizer and facilitator of ecological succession along a glacier forefield chronosequence at the retreating Conejeras glacier in the Tropical Andes. We used the point-intercept method to estimate surface cover of plants, biocrust, bare ground and rocks, as well as soil surface roughness; and a field soil aggregate kit to estimate soil stability. As hypothesized, following a bare-ground stage near the edge of the glacier, the successional trajectory involved the development of a biocrust belt, including bryophytes and lichens, followed by an increasing vascular plant cover. The development of biocrust was accompanied by higher soil surface roughness and soil stability, which likely increased seed entrapment and seedling establishment. Our results suggest that the development of cyanobacterial-dominated biocrust at the forefield of the Conejeras glacier may favor the establishment of plants with large seeds, such as graminoids from the Festuca genus. Overall, our findings highlight the key role of biocrusts in the ecological dynamics that follow glacier melt in the Tropical Andes.